2019
DOI: 10.1104/pp.18.01185
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation in 9-Cis-Epoxycartenoid Dioxygenase 3 and ABA Accumulation

Abstract: The stress hormone abscisic acid (ABA) is critical for drought resistance; however, mechanisms controlling ABA levels are unclear. At low water potential, ABA accumulation in the Arabidopsis (Arabidopsis thaliana) accession Shahdara (Sha) was less than that in Landsberg erecta (Ler) or Columbia. Analysis of a Ler 3 Sha recombinant inbred line population revealed a single major-effect quantitative trait locus for ABA accumulation, which included 9-cis-epoxycarotenoid dioxygenase3 (NCED3) as a candidate gene. NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 44 publications
(81 reference statements)
0
28
0
Order By: Relevance
“…Two other interesting ABA signaling related DEGs are two carotenoid dioxygenases (Cc05_g10210, FC = 1.66; Cc08_g05610, FC = −3.36). The gene Cc05_g10210 encodes CcNCED3, a gene involved in ABA synthesis (Kalladan et al 2019) and previously shown to have increased transcript levels in coffee leaves under different water deficits (Simkin et al 2008;Thioune et al 2017). Transcript levels for carotenoid dioxygenase Cc08_g05610, were relatively high initially, dropped significantly as the water deficit increased, then exhibited only a partial recovery after re-watering.…”
Section: Discussionmentioning
confidence: 97%
“…Two other interesting ABA signaling related DEGs are two carotenoid dioxygenases (Cc05_g10210, FC = 1.66; Cc08_g05610, FC = −3.36). The gene Cc05_g10210 encodes CcNCED3, a gene involved in ABA synthesis (Kalladan et al 2019) and previously shown to have increased transcript levels in coffee leaves under different water deficits (Simkin et al 2008;Thioune et al 2017). Transcript levels for carotenoid dioxygenase Cc08_g05610, were relatively high initially, dropped significantly as the water deficit increased, then exhibited only a partial recovery after re-watering.…”
Section: Discussionmentioning
confidence: 97%
“…Members of the NCED family have been shown to encode key rate-limiting enzymes through the oxidative cleavage of cis -epoxycarotenoids in the ABA biosynthetic pathway to accumulate ABA for further signal transduction in order to resist abiotic stresses [ 84 , 85 , 86 , 87 ]. In recent studies, overexpression of AtNCED3 in Arabidopsis enhanced the drought tolerance by promoting the levels of ABA [ 88 , 89 ]. In rice, the overexpression of OsNCED3 resulted in increased ABA content and promote water stress tolerance of the transgenic plants [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…To explore the molecular mechanisms underlying the increased drought tolerance of the transgenic plants heterologously expressing rty, we analyzed the expression of stress-responsive genes during the PEG treatment using an RT-qPCR analysis. Speci cally, we analyzed the expression of the following drought-responsive genes, involved in ABA biosynthesis, catabolism, transport, and signaling: NCED3 (nine cis-epoxycarotenoid dioxygenase 3) [32], ABI1 (ABA insensitive 1) [33], RD29A (responsive to dehydration 29) [34], DREB2A (dehydration responsive element-binding protein 2A) [35], and PP2C (type-2C protein phosphatase) [36]. The expression of RD29A (a stress-responsive marker), and DREB2A (a regulator of many water stress-inducible genes) during PEG treatment was upregulated to a greater extent in the transgenic plants than in the control plants (Fig.…”
Section: Heterologous Expression Of Rty Confers Drought Tolerance To mentioning
confidence: 99%